Modeling and simulation of a wind farm in the presence of power electronic devices for the enhancement of transient stability. (June 2013) - Farhang, Peyman; Jalilzadeh, Saeid; Kazemi, Ahad
A comprehensive comparative study is made of a pitch control system and shunt flexible AC transmission system (FACTS) devices in order to improve large wind farm operation. Transient stability analysis of a large wind farm in the presence of superconducting magnetic energy storage (SMES), static synchronous compensator (STATCOM), static var compensator (SVC) and pitch controller is performed. The proposed control strategy of the STATCOM is based on PWM control; both the angle and the magnitude of the converter output voltage and the proposed SMES control system is based on a PWM voltage-source converter and a two-quadrant DC–DC chopper using an insulated-gate bipolar transistor (IGBT). Furthermore, robust control systems are designed for SVC and pitch controllers. To investigate the operation of the wind farm with contribution of these devices, two scenarios are considered and simulated. First, extensive analysis of a symmetrical three-phase fault and its effects on system operation is carried out. A permanent fault due to unsuccessful reclosing is analysed; this is one of the most noticeable features of this study. PSCAD/EMTDC software is used for modeling and simulation of the system components and proposed control strategies for power electronic interfaces. System performance analysis under different operating conditions and performance indices show the effectiveness of the proposed controllers even when a severe fault is applied.